Exploring the Market Value Chain Dynamics of Chepa (Semi-Fermented Fish): A Promising Solution to Alleviate Nutritional Deficiency - Mst Jannatul Ferdous; Md Shafiqul Islam; Md Samsul Alam; Mohd Golam Quader Khan; Md Rafiqul Bari; Ikramul Hasan; J Khandakar (Research in Agriculture Livestock and Fisheries, 2024)
Chepa, a widely consumed processed fish product in Bangladesh, is prepared through the semi-fermentation process using small fish varieties such as Phaisa and Puti. The study aimed to explore the business dynamics of Chepa production and marketing, focusing on identifying challenges and issues in the process. In the study, focus group discussion (FGD) and face-to-face interviewing were conducted using semi-structured questionnaires. Additionally, PESTLE framework was employed to assess the operational aspects of the Chepa business. The study identified seven key stakeholders in the different nods of the Chepa value chain, highlighting their role alongside supporting entities. The production process involved careful categorization of dried fish based on size and quality. Notable, women constituted predominant workforce in the midstream segment, especially contributing to fish processing. Unlike other food items, Chepa fermenting processes carried out in treated earthen pots without using any chemicals and pesticide, resulting in a distinctive flavor and color. The study underscores the profitability of Chepa industry, although fishermen earned the lowest profit among the shareholders. Furthermore, the declining populations of small fish in water body like haor, posing a threat to their livelihoods. The PESTLE analysis highlighted the importance of an integrated, and multidisciplinary approach to food safety and quality, stressing the importance of training and institutional development. The outcomes of our study offer valuable insights for policymakers and stakeholders, guiding efforts toward establishing a sustainable and resilient Chepa industry. Vol. 10, No. 3, December 2023: 353-366